An evaluation of prevention initiatives by 53 national anti-doping organizations: Achievements and limitations - Katharina Gatterer; Matthias Gumpenberger; Marie Overbye; Bernhard Streicher; Wolfgang Schobersberger; Cornelia Blank (Elsevier, 2020)
Background: One main purpose of the World Anti-Doping Agency was to harmonize anti-doping efforts, including the provision of anti-doping education. A multifaceted approach to doping prevention can play a key role in preventing intentional and unintentional doping. This article aimed to systematically record and evaluate doping prevention approaches in the form of information and education activities of national anti-doping organizations (NADOs) and assess the extent to which a multifaceted doping prevention approach has been realized. Methods: Data on anti-doping information and education activities of 53 NADOs were collected via a survey and an online search of the NADOs' websites. Prevention activities were classified into knowledge focused, affective focused, social skills, life skills, and ethic- and value- based. The implementation of the prevention activities was assessed by 4 independent raters using a modified visual analogue scale. Results: In total, 59% of the NADOs (n = 38) returned the survey and 70% (n = 45) had information available online. The data were combined for the visual analogue scale assessment. Overall, 58% of the NADOs (n = 37) reported offering activities including elements of all 5 approaches. Results of the raters' assessments indicated that the knowledge-focused approach was best implemented; the implementation of the other 4 approaches was largely unsatisfactory. The most common barriers to implementing doping prevention programs reported by the NADOs were lack of resources (n = 26) and difficulties in collaborating with sports organizations (n = 8). Conclusion: Results show a discrepancy between NADOs' self-report data and the implementation assessment. Even though the NADOs indicated otherwise, most of their education-based approaches did not address aspects of the visual analogue scale (e.g., resisting peer pressure) and only a few programs were ongoing. Possible explanations might be found in the reported barriers (e.g., financial). Concrete guidelines defining multifaceted, values-based education, and best practice examples should be developed to indicate how to include all 5 approaches in prevention.